PENENTUAN AWAL BULAN HIJRIAH MENURUT MAZHAB SYAFII - Kusdiyana Kusdiyana (Mahkamah : Jurnal Kajian Hukum Islam, 2020)
The difference in determining the start of the Hijri month, especially the three months that includes certain prayers, namely Ramadan, Syawal and Zulhijah is often a public conversation although these problems have often appeared, they even appear to be on the annual agenda. These differences in turn penetrate into jurisprudence, which in fact is the result of human interpretation which is very thick with the nuances of its application to the activities, habits, time and place of a human community. So it is very appropriate if these problems are also included in the realm of ijtihadi. These differences occur not only between schools but also internal schools, including the internal Syafii Schools, which are the majority of fiqh schools in Indonesia and are established in various parts of the world. The basic problem in this school is related to the determination of the beginning of the Hijri month in a state that the new moon cannot be rukyah. One opinion says it must be with istikmal (rukyah-istikmal) and the other one says it with hisab.